Elastic wave propagation study in copper poly-grain sample using FEM - Sudhakar Matle (Theoretical and Applied Mechanics Letters, 2017)
The paper presents Voronoi based micro-structure modeling through elastic wave propagation in a poly-crystalline copper using finite element method. The micro-structural parameters studied here are; the grain size and the grain orientation. The poly-crystalline copper is modeled as a randomly oriented Voronoi cells in a fixed 2D computational domain. Tone burst 3-cycle pulse of 1 MHz frequency is used as the line source or point source for testing. Welded contact conditions are used at the interface boundaries of any two mutual cells of the domain. It is reported that wave scattering independent of the shape when the size of the scatterer less than the wavelength. Also, It is concluded that transmission efficiency increases as the cell size decreases.